If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-z/4=3/4
We move all terms to the left:
-z/4-(3/4)=0
We add all the numbers together, and all the variables
-z/4-(+3/4)=0
We get rid of parentheses
-z/4-3/4=0
We multiply all the terms by the denominator
-z-3=0
We add all the numbers together, and all the variables
-1z-3=0
We move all terms containing z to the left, all other terms to the right
-z=3
z=3/-1
z=-3
| 73=19-13w-4w | | x-9+2x-5=2x | | x2+3x+25=0 | | 4w-13w-19=73 | | (2x+4)^2=0 | | 6+2x-10=-8 | | 2^2x-4=64 | | (a+4)^2+45=0 | | 7p-16=22 | | (2x-5)=(4x-10) | | –2x+12=4 | | 2h-10=4h-6 | | 86z+476-367*43775=36767878 | | -4+x+9=7 | | 264=2w^2+2w | | 7x+121=180 | | 35=u/3+14 | | 2m-4/3m=2/3m-1/9 | | (2x+6)=40 | | 5y+9=209 | | 6x*40=23 | | 4l=4 | | 4(b+3)=36 | | 3/4r-2=22 | | 12l=60 | | 2(3x-1)=3(1-2x) | | x-0.3=150 | | -8(3v-3)=4(-4v+8) | | m+8/4=-10 | | (7x+25)=60 | | 5q=40 | | 9+3/2s-8=2s-23 |